Koordinasi Pelaksanaan Program Pemberian Makanan Tambahan Anak Sekolah (Pmt-As) Di Kota Padang - Rini Rahayu; Roni Ekha Putera; Roza Liesmana (Jurnal Administrasi Publik dan Pembanguan, 2019)
In order to improve health while increasing the physical and nutritional resistance of children at school and to encourage interest and learning abilities, the government issued a supplementary program for the provision of school children (PMT-AS) which was also carried out in the city of Padang involving many sectors starting from the city level, sub-district level, village level and school level. In this study, with the involvement of the sector and occurring at the level of the government hierarchy, this paper will examine how to coordinate the implementation of the PMT-AS program in Padang City. The research method used is a qualitative approach. The results of the study showed that the coordination that was carried out in the implementation of the PMT-AS program in Padang City had not run optimally.